Rootstock affects phytotechnical attributes, gas exchange, and carbohydrate accumulation in mango scion - Santos Adriana da Silva; Gomes Fernando Antonio Lima; Silva Luan dos Santos; Neto Vespasiano Borges de Paiva; Silva Maiara Tatiane Lima; Silva Ana Carolina Rodrigues da; Cavalcante Ítalo Herbert Lucena (Folia Horticulturae)
The market demand for grafted mango seedlings is increasing because they provide uniformity and precocity for orchards and gain in productive performance. However, studies on suitable rootstocks for mango seedling production of the main mango cultivars of economic interest in the Sao Francisco Valley, Brazil, are incipient. In this context, the objective of the present study was to evaluate growth, gas exchange, and carbohydrate accumulation in the 'Palmer', 'Tommy Atkins', 'Kent', and 'Keitt' mango scions grafted onto polyembryonic rootstocks ('Capucho', 'Coquinho', and 'Espada'). The experiment was carried out under nursery conditions, with 50% shading. A randomized block experimental design was used, in a 3 × 4 factorial arrangement, consisting of three mango rootstocks ('Espada', 'Capucho', and 'Coquinho') and four mango scion cultivars ('Palmer', 'Keitt', 'Kent', and 'Tommy Atkins'), with five replications and five plants per plot. Graft success was evaluated 28 days after grafting (DAG) to determine the effects of the rootstocks on each scion. Growth, photosynthetic parameters, and total soluble carbohydrate (TSC) and starch content were evaluated 227 DAG. The rootstocks used affected the growth, photosynthetic pigments, contents of TSC and starch, and gas exchange of the mango scions. The higher graft success percentages were found for the cultivars 'Keitt', 'Palmer', and 'Kent' grafted on 'Espada' rootstocks. The cultivar 'Tommy Atkins' showed the highest graft success percentages when grafted on 'Espada' and 'Capucho' rootstocks. 'Capucho' rootstocks showed higher performance for most of the analysed variables, mainly when using 'Palmer' and 'Tommy Atkins' cultivars as scions.